2015
DOI: 10.4314/ijbcs.v9i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Dichloro-diphenyl-trichloro-ethane (DDT) and hexachlorohexane (HCH) pesticide residues in foodstuffs from markets in Ile-Ife, Nigeria

Abstract: Levels of dichlorodiphenyltrichloroethanes (DDTs) and Hexachlorocyclohexanes (HCHs) pesticide were evaluated in samples of cowpea grains and dried yam chips obtained from Ile-Ife markets, southwestern Nigeria. The objectives of the study were to establish the presence of the organochlorine pesticide residues in the foodstuffs and also to ascertain whether the residue levels are above their respective permissible levels. Randomly selected samples from highly patronized markets were subjected to standard extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…For example, Fianko et al (2013) found high ratios of DDE/DDT in fish samples (with a mean of 2.51) indicating old input of DDT and significant degradation. Similarly, the study by Sosan et al (2015) found higher concentrations of p,p'-DDD and p,p'-DDE than the concentrations of p,p'-DDT in foodstuffs from markets in Ile-Ife, Nigeria indicating that the DDT had substantially metabolized into DDD and DDE.…”
Section: Discussion Profiles Of the Pesticide Residuesmentioning
confidence: 79%
“…For example, Fianko et al (2013) found high ratios of DDE/DDT in fish samples (with a mean of 2.51) indicating old input of DDT and significant degradation. Similarly, the study by Sosan et al (2015) found higher concentrations of p,p'-DDD and p,p'-DDE than the concentrations of p,p'-DDT in foodstuffs from markets in Ile-Ife, Nigeria indicating that the DDT had substantially metabolized into DDD and DDE.…”
Section: Discussion Profiles Of the Pesticide Residuesmentioning
confidence: 79%
“…In another study of OCPs in cowpeas from markets in Ile-Ife, southwestern Nigeria, the concentration ranges for alpha-, beta-, and delta-BHC were between 7 to 44 ng/g, 11 to 144 ng/g and 19 to 125 ng/g, respectively. 32 In another study in Lagos, Nigeria, the mean concentration of aldrin, DDT, dieldrin, endosulfan and endrin residues in beans was 9.8, 35.1, 5.8, 22.5 and 7.8 ng/g, respectively. 33 Based on this and other studies conducted in Nigeria on the levels of OCPs in foods, concentrations of OCPs were lower than those reported from other parts of the world.…”
Section: Discussionmentioning
confidence: 93%
“…. The cyclodienes group which include dieldrin, aldrin, endrin and endosulfan have been reported in some food products in Nigeria [30,31,34]. The mean concentration of aldrin was 0.156 mg kg -1 , while the mean concentration of endosulfan metabolite gave 0.076 mg kg -1 αendosulfan, 0.243 mg kg -1 β-endosulfan and 0.218 mg kg -1 endosulfan sulphate with total endosulfan concentration of 0.537 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In West Africa, many studies have reported contamination levels of pesticide residues in fruits and vegetables [19,20,21,22,23,24] and in maize and cowpea [25]. In Nigeria, several studies have also reported high levels of pesticide residues in fruits, vegetables and other food crops produce [26,27,28,29,30,31], on cocoa [32] and on kolanut [33] as well as seafood products [34].…”
Section: Introductionmentioning
confidence: 99%